Moscas Ectoparasitas (Diptera: Hippoboscoidea) de Morcegos (Mammalia: Chiroptera) no Estado do Maranhão - DIAS, Paulo Adriano (2008)
This list of species is the first study dealing with bat flies in the Maranhão State. The work was done at seven different areas in the cities Bacabeira, São Luis, Santa Inês and Tufilândia. The bats were captured in mists nets and the parasites were collected with tweezers. A total of 559 bat flies belonging to 25 species, (22 species of the family Streblidae and 2 of Nycteribiidae), were colleted from 118 bats belonging to 22 species, 13 genera and 4 families. Trichobius joblingi Wenzel, 1966 was the most frequent species with 28.7% of the collected individuals. This study registered a high number of species of bat flies in the state, evidencing the importance of the area for studies of biodiversity, as well as aspects related to host-parasite relationships.